Effects of Moxifloxacin on Human Neutrophil and T-Lymphocyte Functions in Vitro - Ronald Anderson; Riana Cockeran; Charles Feldman; Annette J Theron; Moliehi Potjo (MDPI AG, 2010)
Moxifloxacin is useful in the treatment of respiratory infections, including community-acquired pneumonia, and also shows promise in the treatment of tuberculosis, a clinical setting which necessitates extended administration of this agent. Relatively little is known, however, about the effects of this agent on the antimicrobial and proliferative activities of human neutrophils and T-lymphocytes, respectively. In the current study, we have investigated the effects of moxifloxacin at therapeutic concentrations and greater (1-20 µg/mL) on cytosolic Ca2+ fluxes, generation of antimicrobial reactive oxygen species (ROS), and release of the primary granule protease, elastase, following activation of the cells with the chemoattractant, fMLP (1 µM), or the phorbol ester, PMA (25 ng/mL), using radiometric, chemiluminescence, and colourimetric procedures, respectively. The effects of moxifloxacin on mitogen-activated proliferation of T cells and expression of the interleukin-2 (IL-2) receptor (CD25) were measured using radiometric and flow cytometric procedures respectively. With the exception of elastase release, which was significantly increased (P < 0.05) by treatment of the cells with moxifloxacin at 10 and 20 µg/mL, none of the other neutrophil or lymphocyte functions was affected by moxifloxacin. These observations suggest that extended use of this agent is unlikely to compromise the protective functions of neutrophils and T-lymphocytes and may even potentiate neutrophil-mediated antimicrobial activity by increasing the release of elastase.